The Effect of Financial Experience and Overconfidence on Investment Decisions with Locus of Control as an Intervening Variable - Fajri Akbar; Gatot Nazir Ahmad; Agung Dharmawan Buchdadi (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to determine the effect of financial experience and overconfidence on investment decisions with locus of control as an intervening variable. The method used in this study is quantitative research. The sampling technique employed in the study is Convenience Sampling. The sample consists of 140 investors who have a steady income and reside in the Greater Jakarta area (Jabodetabek). The data in this study was processed using SmartPLS 3 with the Structural Equation Modeling (SEM) method. The results of this study indicate that financial experience and locus of control have a positive and significant effect on investment decisions. Overconfidence has a negative and significant effect on investment decisions. Financial experience has a positive and significant effect on locus of control. Overconfidence has a negative and significant effect on locus of control. Locus of control mediates the effect of financial experience and overconfidence on investment decisions.